Investigating the chemical constituent and the suppressive effects of alliin hydrolysate on E.coli - Tao Wu; Ning Chen; Chang Liu; Rui Liu; Jiaojiao Zhang; Xuan Xie; Min Zhang (Natural Product Research, 2017)

Photoperiodism dynamics during the domestication and improvement of soybean - Sheng-Rui Zhang; Huan Wang; Zhongyu Wang; Yao Ren; Lifang Niu; Jun Liu; Bin Liu (Science China Life Sciences, 2017)

Propagation of the Stress Wave Through the Filled Joint with Linear Viscoelastic Deformation Behavior Using Time-Domain Recursive Method - Rui Wang; Zhiping Hu; Dan Zhang; Qiyao Wang (Rock Mechanics and Rock Engineering, 2017)

Activation of Alpha-7 Nicotinic Acetylcholine Receptor Reduces Brain Edema in Mice with Ischemic Stroke and Bone Fracture - Dingquan Zou; Man Luo; Zhenying Han; Lei Zhan; Wan Zhu; Shuai Kang; Chen Bao; Zhao Li; Jeffrey Nelson; Rui Zhang; Hua Su (Molecular Neurobiology, 2017)

Growth Differentiation Factor 15 Is a Novel Diagnostic Biomarker of Mitochondrial Diseases - Xinbo Ji; Lizhen Zhao; Kunqian Ji; Yuying Zhao; Wei Li; Rui Zhang; Ying Hou; Jianqiang Lu; Chuanzhu Yan (Molecular Neurobiology, 2017)

Synthesis and biological evaluation of disulfides bearing 1,2,4-triazole moiety as antiproliferative agents - Xue-Feng Wang; Shuai Zhang; Bao-Lin Li; Ji-Jun Zhao; Yu-Ming Liu; Rui-Lian Zhang; Bo Li; Bao-Quan Chen (Medicinal Chemistry Research, 2017)

TQ-B3203, a potent proliferation inhibitor derived from camptothecin - Xiquan Zhang; Meng Cao; Jing Xing; Fei Liu; Ping Dong; Xin Tian; Hongjiang Xu; Laifang Zhang; Hongmei Gu; Ling Yang; Rui Li; Ming Zheng; et al. (Medicinal Chemistry Research, 2017)

Mechanisms of Acupuncture Therapy for Cerebral Ischemia: an Evidence-Based Review of Clinical and Animal Studies on Cerebral Ischemia - Wen Zhu; Yang Ye; Yi Liu; Xue-Rui Wang; Guang-Xia Shi; Shuai Zhang; Cun-Zhi Liu (Journal of Neuroimmune Pharmacology, 2017)

A two-step ionospheric modeling algorithm considering the impact of GLONASS pseudo-range inter-channel biases - Rui Zhang; Yi-bin Yao; Yue-ming Hu; Wei-wei Song (Journal of Geodesy, 2017)

Flocculation of coal washing wastewater using polysaccharide produced by Paenibacillus mucilaginosus WL412 - Haiyang Xu; Jing Li; Renjie Fu; Rui Cheng; Shiming Wang; Jianfa Zhang (Environmental Science and Pollution Research, 2017)

Residents’ environmental conservation behaviour in the mountain tourism destinations in China: Case studies of Jiuzhaigou and Mount Qingcheng - Yu-ling Zhang; Jie Zhang; Hong-ou Zhang; Ruo-yang Zhang; Yang Wang; Yong-rui Guo; Zong-cai Wei (Journal of Mountain Science, 2017)

Structural Transformation Detection Contributes to Screening of Behaviorally Active Compounds: Dynamic Binding Process Analysis of DhelOBP21 from Dastarcus helophoroides - Rui-Nan Yang; Dong-Zhen Li; Guangqiang Yu; Shan-Cheng Yi; Yinan Zhang; De-Xin Kong; Man-Qun Wang (Journal of Chemical Ecology, 2017)

Development and characterization of 32 SNP markers for the northern snakehead (Channa argus) using high resolution melting (HRM) - Bo-Chi Zhang; Gui-Rong Zhang; Wei Ji; Rui-Bin Yang; Gui-Wei Zou; Kun-Ci Chen; Kai-Jian Wei; Jonathan P. A. Gardner (Conservation Genetics Resources, 2017)

Polyamine-binding protein PotD2 is required for stress tolerance and virulence in Actinobacillus pleuropneumoniae - Zhuang Zhu; Qin Zhao; Yu Zhao; Fei Zhang; Xintian Wen; Xiaobo Huang; Yiping Wen; Rui Wu; Qigui Yan; Yong Huang; Xiaoping Ma; Xinfeng Han; et al. (Antonie van Leeuwenhoek, 2017)

Creation of miniature pig model of human Waardenburg syndrome type 2A by ENU mutagenesis - Tang Hai; Weiwei Guo; Jing Yao; Chunwei Cao; Ailing Luo; Meng Qi; Xianlong Wang; Xiao Wang; Jiaojiao Huang; Ying Zhang; Hongyong Zhang; Dayu Wang; et al. (Human Genetics, 2017)

The responses of two native plant species to soil petroleum contamination in the Yellow River Delta, China - Wenjun Xie; Yanpeng Zhang; Rui Li; Hongjun Yang; Tao Wu; Liping Zhao; Zhaohua Lu (Environmental Science and Pollution Research, 2017)

White Matter Connectivity Pattern Associate with Characteristics of Scalp EEG Signals - Jinnan Gong; Cheng Luo; Xuebin Chang; Rui Zhang; Benjamin Klugah-Brown; Lanjin Guo; Peng Xu; Dezhong Yao (Brain Topography, 2017)

Thermal recovery process of a backfilled open-pit in permafrost area at the Gulian strip coal mine in Northeast China - Shu-hui Gao; Rui-xia He; Hui-jun Jin; Ya-dong Huang; Jian-ming Zhang; Dong-liang Luo (Journal of Mountain Science, 2017)

Breaking the sporoderm of Ganoderma lucidum spores by combining chemical reaction with physical actuation - Jiajia Wang; Rui Ke; Shengyi Zhang (Natural Product Research, 2017)

Voronoi Cell Finite Element Method for Fluid-Filled Materials - Rui Zhang; Ran Guo (Transport in Porous Media, 2017)

Attenuation of ethanol abstinence-induced anxiety- and depressive-like behavior by the phosphodiesterase-4 inhibitor rolipram in rodents - Mei-Fang Gong; Rui-Ting Wen; Ying Xu; Jian-Chun Pan; Ning Fei; Yan-Meng Zhou; Jiang-Ping Xu; Jian-Hui Liang; Han-Ting Zhang (Psychopharmacology, 2017)

Populus euphratica J3 mediates root K+/Na+ homeostasis by activating plasma membrane H+-ATPase in transgenic Arabidopsis under NaCl salinity - Yinan Zhang; Yang Wang; Gang Sa; Yuhong Zhang; Jiayin Deng; Shurong Deng; Meijuan Wang; Huilong Zhang; Jun Yao; Xiuying Ma; Rui Zhao; Xiaoyang Zhou; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2017)

Association of ACYP2 and TSPYL6 Genetic Polymorphisms with Risk of Ischemic Stroke in Han Chinese Population - Yiqian Liang; Rui Zhang; Shuo Zhang; Guofa Ji; Puyu Shi; Tian Yang; Feng Liu; Jing Feng; Chunqi Li; Dangshe Guo; Mingwei Chen (Molecular Neurobiology, 2017)

Limit Analysis of Roof Falling in Roadway with Water-Rich Surrounding Rock - Bei Jiang; Qi Wang; Li Gao; Shucai Li; Chong Zhang; Hongke Gao; Rui Pan (Geotechnical and Geological Engineering, 2017)

Protective effect of Ganoderma lucidum polysaccharide against carbon tetrachloride-induced hepatic damage in precision-cut carp liver slices - Yingjuan Liu; Chunyun Zhang; Jinliang Du; Rui Jia; Liping Cao; Galina Jeney; Hiroki Teraoka; Pao Xu; Guojun Yin (Fish Physiology and Biochemistry, 2017)

Assessment of PPP integer ambiguity resolution using GPS, GLONASS and BeiDou (IGSO, MEO) constellations - Yanyan Liu; Yidong Lou; Shirong Ye; Rui Zhang; Weiwei Song; Xing Zhang; Qingquan Li (GPS Solutions, 2017)

Comparative study of the leaf transcriptomes and ionoms of Juglans regia and its wild relative species Juglans cathayensis - Zhongcheng Zhou; Muxian Han; Mei Hou; Xiaojing Deng; Rui Tian; Shuifa Min; Jinbo Zhang (Acta Physiologiae Plantarum, 2017)

The ArfGAP protein MoGlo3 regulates the development and pathogenicity of Magnaporthe oryzae - Shengpei Zhang; Xiu Liu; Lianwei Li; Rui Yu; Jialiang He; Haifeng Zhang; Xiaobo Zheng; Ping Wang; Zhengguang Zhang (Environmental Microbiology, 2017)
Summary The ADP ribosylation factor (Arf) and the coat protein complex I (COPI) are involved in vesicle transport. Together with GTPase‐activating proteins (ArfGAPs) and guanine exchange factors (ArfGEFs) that regulate the activity of Arf, they govern vesicle formation, COPI trafficking and the maintenance of the Golgi complex. In an ongoing effort to study the role of membrane trafficking in pathogenesis of the rice blast fungus Magnaporthe oryzae , we identified MoGlo3 as an ArfGAP protein that is homologous to Glo3p of the budding yeast Saccharomyces cerevisiae . As suspected, MoGlo3 partially complements the function of yeast Glo3p. Consistent with findings in S. cerevisiae , MoGlo3 is localized to the Golgi, and that the localization is dependent on the conserved BoCCS domain. We found that MoGlo3 is highly expressed during conidiation and early infection stages and is required for vegetative growth, conidial production and sexual development. We further found that the Δ Moglo3 mutant is defective in endocytosis, scavenging of the reactive oxygen species, and in the response to endoplasmic reticulum (ER) stress. The combined effects result in failed appressorium function and decreased pathogenicity. Moreover, we provided evidence showing that the domains including the GAP, BoCCS and GRM are all important for normal MoGlo3 functions. Our studies further illustrate the importance of normal membrane trafficking in the physiology and pathogenicity of the rice blast fungus.

Oligosaccharide elicitor prepared from Salecan triggers the defense responses of Arabidopsis thaliana Col0 against Botrytis cinerea infection - Haiyang Xu; Jing Li; Shiming Wang; Linxiang Xu; Rui Cheng; Jianfa Zhang (World Journal of Microbiology and Biotechnology, 2017)

Rare Genetic Variants of the Transthyretin Gene Are Associated with Alzheimer’s Disease in Han Chinese - Qun Xiang; Rui Bi; Min Xu; Deng-Feng Zhang; Liwen Tan; Chen Zhang; Yiru Fang; Yong-Gang Yao (Molecular Neurobiology, 2017)

Tbx18-dependent differentiation of brown adipose tissue-derived stem cells toward cardiac pacemaker cells - Lei Chen; Zi-Jun Deng; Jian-Sheng Zhou; Rui-Juan Ji; Xi Zhang; Chuan-Sen Zhang; Yu-Quan Li; Xiang-Qun Yang (Molecular and Cellular Biochemistry, 2017)

Behavioral responses of the egg parasitoid Trissolcus japonicus to volatiles from adults of its stink bug host, Halyomorpha halys - Yong-Zhi Zhong; Jin-Ping Zhang; Li-Li Ren; Rui Tang; Hai-Xia Zhan; Guo-Hua Chen; Feng Zhang (Journal of Pest Science, 2017)

Hydrochemical regime and its mechanism in Yamzhog Yumco Basin, South Tibet - Meng Zhe; Xueqin Zhang; Buwei Wang; Rui Sun; Du Zheng (Journal of Geographical Sciences, 2017)

Diffraction separation by plane-wave prediction filtering - Xue Kong; De-Ying Wang; Zhen-Chun Li; Rui-Xiang Zhang; Qiu-Yuan Hu (Applied Geophysics, 2017)

Endothelial Progenitor Cells’ Classification and Application in Neurological Diseases - Jing-jing Yuan; Jing Yang; Shi-lei Sun; Rui Zhang; Yu-ming Xu (Tissue Engineering and Regenerative Medicine, 2017)

Influence of Inoculation of Leifsonia xyli subsp. xyli on Photosynthetic Parameters and Activities of Defense Enzymes in Sugarcane - Xiao-Qiu Zhang; Yong-Jian Liang; Kai Zhu; Chao-Xing Wu; Li-Tao Yang; Yang-Rui Li (Sugar Tech, 2017)

Phenotypic Variation and Genetic Diversity in the Collections of Erianthus Arundinaceus (Retz.) Jesw. - Xi-Hui Liu; Huan-Zhong Song; Ge-Min Zhang; Wei-Xing Duan; Rong-Hua Zhang; Yang-Rui Li (Sugar Tech, 2017)

Correlation of rs9331888 polymorphism with Alzheimer’s disease among Caucasian and Chinese populations: a meta-analysis and systematic review - Bin Zhu; Rui Min Wang; Jian Ting Wang; Rui Ling Chen; Yan Fei Zheng; Lei Zhang; Zhi Gang Zhao (Metabolic Brain Disease, 2017)

Memantine Can Reduce Ethanol-Induced Caspase-3 Activity and Apoptosis in H4 Cells by Decreasing Intracellular Calcium - Xiaolong Wang; Jiajun Chen; Hongbo Wang; Hao Yu; Changliang Wang; Jiabin You; Pengfei Wang; Chunmei Feng; Guohui Xu; Xu Wu; Rui Zhao; Guohua Zhang (Journal of Molecular Neuroscience, 2017)

Inhibitory effect of StCYP707A1 gene on tuberization in transgenic potato - Lu Liu; Rui-Jie Zhang; Wen-Jiao Zhu; Xin-Ru Liu; Ke Shi; Min Chen; Qing Yang (Plant Biotechnology Reports, 2017)

Genesis and tectonic setting of the Late Devonian Tawuerbieke gold deposit in the Tulasu ore cluster, western Tianshan, Xinjiang, China - Yi-Wei Peng; Xue-Xiang Gu; Peng-Rui Lv; Yong-Mei Zhang; Wen-Bin Cheng; Xin-Li Wang (International Geology Review, 2017)

A simple method for removing low-density granulocytes to purify T lymphocytes from peripheral blood mononuclear cells - Si-gong Zhang; Yu-xin Song; Xiao-ming Shu; Hai-li Shen; Han-bo Yang; Rui-xue Duo; Guo-chun Wang (Journal of Zhejiang University-SCIENCE B, 2017)

Puerarin may protect against Schwann cell damage induced by glucose fluctuation - Bing Xue; Lin Wang; Zhe Zhang; Rui Wang; Xin-xin Xia; Ping-ping Han; Li-jun Cao; Yong-hui Liu; Lian-qing Sun (Journal of Natural Medicines, 2017)

Phosphorylation of histone H3 on Ser-10 by Aurora B is essential for chromosome condensation in porcine embryos during the first mitotic division - Changchao Chen; Zixiao Zhang; Panpan Cui; Yaya Liao; Yue Zhang; Lingyun Yao; Rong Rui; Shiqiang Ju (Histochemistry and Cell Biology, 2017)

Holocene activity evidence on the southeast boundary fault of Heqing basin, middle segment of Heqing-Eryuan fault zone, West Yunnan Province, China - Chang-bin Sun; De-wen Li; Xiao-ming Shen; Yan-rui Kang; Rui Liu; Ya-jiao Zhang (Journal of Mountain Science, 2017)

New optimal smoothing scheme for improving relative and absolute accuracy of tightly coupled GNSS/SINS integration - Xiaohong Zhang; Feng Zhu; Xianlu Tao; Rui Duan (GPS Solutions, 2017)

A Shinella β-N-acetylglucosaminidase of glycoside hydrolase family 20 displays novel biochemical and molecular characteristics - Junpei Zhou; Zhifeng Song; Rui Zhang; Caihong Chen; Qian Wu; Junjun Li; Xianghua Tang; Bo Xu; Junmei Ding; Nanyu Han; Zunxi Huang (Extremophiles, 2017)

Stability design charts for homogeneous slopes under typical conditions based on the double shear strength reduction technique - Gaopeng Tang; Lianheng Zhao; Li Liang; Shi Zuo; Rui Zhang (Arabian Journal of Geosciences, 2017)

Erratum to: Transposon insertion resulted in the silencing of Wx-B1n in Chinese wheat landraces - Ling‑Ling Zhang; Hu Chen; Mi Luo; Xiao‑Wei Zhang; Mei Deng; Jian Ma; Peng‑Fei Qi; Ji‑Rui Wang; Guo‑Yue Chen; Ya‑Xi Liu; Zhi‑En Pu; Wei Li; et al. (Theoretical and Applied Genetics, 2017)

Transposon insertion resulted in the silencing of Wx-B1n in Chinese wheat landraces - Ling-Ling Zhang; Hu Chen; Mi Luo; Xiao-Wei Zhang; Mei Deng; Jian Ma; Peng-Fei Qi; Ji-Rui Wang; Guo-Yue Chen; Ya-Xi Liu; Zhi-En Pu; Wei Li; et al. (Theoretical and Applied Genetics, 2017)

Anatomy of composition and nature of plate convergence: Insights for alternative thoughts for terminal India-Eurasia collision - WenJiao Xiao; SongJian Ao; Lei Yang; ChunMing Han; Bo Wan; Ji’En Zhang; ZhiYong Zhang; Rui Li; ZhenYu Chen; ShuaiHua Song (Science China Earth Sciences, 2017)

Bioactivity, toxicity and detoxification assessment of Dioscorea bulbifera L.: a comprehensive review - Xiao-Rui Guan; Lin Zhu; Zhan-Gang Xiao; Yi-Lin Zhang; Hu-Biao Chen; Tao Yi (Phytochemistry Reviews, 2017)

Apigenin attenuates streptozotocin-induced pancreatic β cell damage by its protective effects on cellular antioxidant defense - Ning Wang; Wen Jing Yi; Lu Tan; Jia Hui Zhang; Jiamin Xu; Yi Chen; Mengting Qin; Shuang Yu; Jing Guan; Rui Zhang (In Vitro Cellular & Developmental Biology - Animal, 2017)

Fluctuating asymmetry rather than oxidative stress in Bufo raddei can be an accurate indicator of environmental pollution induced by heavy metals - Rui Guo; Wenya Zhang; Shiwei Ai; Liang Ren; Yingmei Zhang (Environmental Monitoring and Assessment, 2017)

Characterization and speciation of mercury in mosses and lichens from the high-altitude Tibetan Plateau - Jun-juan Shao; Cheng-bin Liu; Qing-hua Zhang; Jian-jie Fu; Rui-qiang Yang; Jian-bo Shi; Yong Cai; Gui-bin Jiang (Environmental Geochemistry and Health, 2017)

Formation and evolution of Emeishan basalt saprolite in vadose zones of Touzhai landslide source rockmass - Ji-qing Yang; Ze-min Xu; Rui Zhang; Ji-pu Chen; Zhe Ren; Rong-zhang Luo; Xiu-shuo Zhang (Journal of Mountain Science, 2017)

Ne2 encodes protein(s) and the altered RuBisCO could be the proteomics leader of hybrid necrosis in wheat (Triticum aestivum L.) - Si Rui Pan; Xing Lai Pan; Qian Ying Pan; Yin Hong Shi; Li Zhang; Yun Fan; Yan Rui Xue (Journal of Genetics, 2017)

Research and application of spectral inversion technique in frequency domain to improve resolution of converted PS-wave - Hua Zhang; Zhen-Hua He; Ya-Lin Li; Rui Li; Guamg-Ming He; Zhong Li (Applied Geophysics, 2017)

Synthesis and fungicidal activity of tryptophan analogues – the unexpected calycanthaceous alkaloid derivatives - Shaojun Zheng; Yongdong Gu; Longbo Li; Rui Zhu; Xingwei Cai; Hongjin Bai; Jiwen Zhang (Natural Product Research, 2017)

Assessment of Correlation Between Early and Late Efficacy Endpoints to Identify Potential Surrogacy Relationships in Non-Hodgkin Lymphoma: a Literature-Based Meta-analysis of 108 Phase II and Phase III Studies - Rui Zhu; Dan Lu; Yu-Waye Chu; Akiko Chai; Michelle Green; Nancy Zhang; Jin Yan Jin (The AAPS Journal, 2017)

Increased lateral root formation by CRISPR/Cas9-mediated editing of arginase genes in cotton - Yanling Wang; Zhigang Meng; Chengzhen Liang; Zhaohong Meng; Yuan Wang; Guoqing Sun; Tao Zhu; Yongping Cai; Sandui Guo; Rui Zhang; Yi Lin (Science China Life Sciences, 2017)

Paleogene-Neogene stratigraphic realm and tectonic-sedimentary evolution of the Qilian Mountains and their surrounding areas - LiRong Yang; JianXing Li; LePing Yue; HongLiang Wang; HuaiJun Guo; XiaoHui Zhu; Tao Zhu; Kai Du; Rui Zhang; YunXiang Zhang; HuJun Gong (Science China Earth Sciences, 2017)

Pollen dispersal, mating patterns and pollen contamination in an insect-pollinated seed orchard of Schima superba Gardn. et Champ. - Hanbo Yang; Rui Zhang; Zhichun Zhou (New Forests, 2017)

Isorhamnetin protects against cardiac hypertrophy through blocking PI3K–AKT pathway - Lu Gao; Rui Yao; Yuzhou Liu; Zheng Wang; Zhen Huang; Binbin Du; Dianhong Zhang; Leiming Wu; Lili Xiao; Yanzhou Zhang (Molecular and Cellular Biochemistry, 2017)

Intelligent diagnosis of jaundice with dynamic uncertain causality graph model - Shao-rui Hao; Shi-chao Geng; Lin-xiao Fan; Jia-jia Chen; Qin Zhang; Lan-juan Li (Journal of Zhejiang University-SCIENCE B, 2017)

Phytotoxicity of CeO2 nanoparticles on radish plant (Raphanus sativus) - Xin Gui; Mengmeng Rui; Youhong Song; Yuhui Ma; Yukui Rui; Peng Zhang; Xiao He; Yuanyuan Li; Zhiyong Zhang; Liming Liu (Environmental Science and Pollution Research, 2017)

Microbial profiles of a drinking water resource based on different 16S rRNA V regions during a heavy cyanobacterial bloom in Lake Taihu, China - Junyi Zhang; Congming Zhu; Rui Guan; Zhipeng Xiong; Wen Zhang; Junzhe Shi; Yi Sheng; Bingchuan Zhu; Jing Tu; Qinyu Ge; Ting Chen; Zuhong Lu (Environmental Science and Pollution Research, 2017)

Morphological and molecular identification of Habronema spp. (Nematoda: Habronematidae) from donkeys in Xinjiang, China, and notes on the taxonomical status of Habronema majus (Creplin, 1849) and H. microstoma (Schneider, 1866) - Rui Jian; Shi-Wei Wang; Wei-Xin Zhang; Lu-Ping Zhang (Systematic Parasitology, 2017)

Waterlogging risk assessment based on self-organizing map (SOM) artificial neural networks: a case study of an urban storm in Beijing - Wen-li Lai; Hong-rui Wang; Cheng Wang; Jie Zhang; Yong Zhao (Journal of Mountain Science, 2017)

Rhizobium rhizosphaerae sp. nov., a novel species isolated from rice rhizosphere - Juan-Juan Zhao; Jun Zhang; Rui-Jie Zhang; Cai-Wen Zhang; Hua-Qun Yin; Xiao-Xia Zhang (Antonie van Leeuwenhoek, 2017)

Carboxyamidotriazole alleviates muscle atrophy in tumor-bearing mice by inhibiting NF-κB and activating SIRT1 - Chen Chen; Rui Ju; Lei Zhu; Juan Li; Wei Chen; De-chang Zhang; Cai-ying Ye; Lei Guo (Naunyn-Schmiedeberg's Archives of Pharmacology, 2017)

The OPA1 Gene Mutations Are Frequent in Han Chinese Patients with Suspected Optic Neuropathy - A-Mei Zhang; Rui Bi; Qiu-Xiang Hu; Yu Fan; Qingjiong Zhang; Yong-Gang Yao (Molecular Neurobiology, 2017)

Does residual H2O2 result in inhibitory effect on enhanced anaerobic digestion of sludge pretreated by microwave-H2O2 pretreatment process? - Jibao Liu; Ruilai Jia; Yawei Wang; Yuansong Wei; Junya Zhang; Rui Wang; Xing Cai (Environmental Science and Pollution Research, 2017)

Adenosine A2A receptors in the olfactory bulb suppress rapid eye movement sleep in rodents - Yi-Qun Wang; Rui Li; Dian-Ru Wang; Yoan Cherasse; Ze Zhang; Meng-Qi Zhang; Oriana Lavielle; Kristopher McEown; Serge N. Schiffmann; Alban de Kerchove d’Exaerde; Wei-Min Qu; Michael Lazarus; et al. (Brain Structure and Function, 2017)

GLONASS phase bias estimation and its PPP ambiguity resolution using homogeneous receivers - Yanyan Liu; Weiwei Song; Yidong Lou; Shirong Ye; Rui Zhang (GPS Solutions, 2017)

Assessing the vulnerability of changing coasts, Hainan Island, China - Yaping Wang; Benwei Shi; Liang Zhang; Jianjun Jia; Xiaomin Xia; Liang Zhou; Rui Yu; Yang Yang; Jianhua Gao (Acta Oceanologica Sinica, 2017)

Physiological characteristics and metabolomics of transgenic wheat containing the maize C4 phosphoenolpyruvate carboxylase (PEPC) gene under high temperature stress - Xueli Qi; Weigang Xu; Jianzhou Zhang; Rui Guo; Mingzhong Zhao; Lin Hu; Huiwei Wang; Haibin Dong; Yan Li (Protoplasma, 2017)

Genotoxicity and cytotoxicity reduction of the polluted urban river after ecological restoration: a field-scale study of Jialu River in northern China - Jie Sun; Rui Zhang; Long Qin; Haixiao Zhu; Yu Huang; Yingang Xue; Shuqing An; Xianchuan Xie; Aimin Li (Environmental Science and Pollution Research, 2017)

Characterization of a neutral recombinant xylanase from Thermoactinospora rubra YIM 77501T - Yi-Rui Yin; Qing-Wen Hu; Wen-Dong Xian; Feng Zhang; En-Min Zhou; Hong Ming; Min Xiao; Xiao-Yang Zhi; Wen-Jun Li (Antonie van Leeuwenhoek, 2017)

Cloning and expression of Perilla frutescens FAD2 gene and polymorphism analysis among cultivars - Yufei Xue; Xingcui Zhang; Rui Wang; Baojun Chen; Jiayi Jiang; Aung Naing Win; Yourong Chai (Acta Physiologiae Plantarum, 2017)

Isolation, chemical characterization, and immunomodulatory activity of naturally acetylated hemicelluloses from bamboo shavings - Ju-qing Huang; Rui-ting Qi; Mei-rong Pang; Cong Liu; Guang-yu Li; Ying Zhang (Journal of Zhejiang University-SCIENCE B, 2017)

Blood Flow and Oxygen Transport in Descending Branch of Lateral Femoral Circumflex Arteries After Transfemoral Amputation: A Numerical Study - Fei Yan; Wen-Tao Jiang; Rui-Qi Dong; Qing-Yuan Wang; Yu-Bo Fan; Ming Zhang (Journal of Medical and Biological Engineering, 2017)

Demethyleneberberine alleviates inflammatory bowel disease in mice through regulating NF-κB signaling and T-helper cell homeostasis - Ying-Ying Chen; Rui-Yan Li; Mei-Jing Shi; Ya-Xing Zhao; Yan Yan; Xin-Xin Xu; Miao Zhang; Xiao-Tong Zhao; Yu-Bin Zhang (Inflammation Research, 2017)

Validation of the quantitative trait locus underlying soybean plant height using residual heterozygous lines and near-isogenic lines across multi-environments - Long Yan; Yuanyuan Zhang; Qijian Song; Perry B. Cregan; Chunyan Yang; Yongqiang Charles An; Chengjun Wu; Qiang Chen; Bingqiang Liu; Rui Di; Mengchen Zhang (Euphytica, 2017)

Ammonium inhibition through the decoupling of acidification process and methanogenesis in anaerobic digester revealed by high throughput sequencing - Miao Zhang; Qiang Lin; Junpeng Rui; Jiabao Li; Xiangzhen Li (Biotechnology Letters, 2017)

Dietary Zinc Oxide Modulates Antioxidant Capacity, Small Intestine Development, and Jejunal Gene Expression in Weaned Piglets - Cui Zhu; Hang Lv; Zhuang Chen; Li Wang; Xiuju Wu; Zhongjian Chen; Weina Zhang; Rui Liang; Zongyong Jiang (Biological Trace Element Research, 2017)

The transgenic expression of human follistatin-344 increases skeletal muscle mass in pigs - Fei Chang; Rui Fang; Meng Wang; Xin Zhao; Wen Chang; Zaihu Zhang; Ning Li; Qingyong Meng (Transgenic Research, 2017)

Characterization of uncultivated magnetotactic bacteria from the sediments of Yuehu Lake, China - Haijian Du; Rui Zhang; Wenyan Zhang; Cong Xu; Yiran Chen; Hongmiao Pan; Ke Zhou; Long-fei Wu; Tian Xiao (Acta Oceanologica Sinica, 2017)

Study on Enhanced Dissolution of Azilsartan-Loaded Solid Dispersion, Prepared by Combining Wet Milling and Spray-Drying Technologies - Tianshu Lu; Yinghua Sun; Dawei Ding; Qi Zhang; Rui Fan; Zhonggui He; Jing Wang (AAPS PharmSciTech, 2017)

Hydrogen‐rich water regulates effects of ROS balance on morphology, growth and secondary metabolism via glutathione peroxidase in Ganoderma lucidum - Ang Ren; Rui Liu; Zhi‐Gang Miao; Xue Zhang; Peng‐Fei Cao; Tian‐Xi Chen; Chen‐Yang Li; Liang Shi; Ai‐Liang Jiang; Ming‐Wen Zhao (Environmental Microbiology, 2017)
Summary Ganoderma lucidum is one of the most important medicinal fungi, but the lack of basic study on the fungus has hindered the further development of its value. To investigate the roles of the redox system in G. lucidum , acetic acid (HAc) was applied as a reactive oxygen species (ROS) stress inducer, and hydrogen‐rich water (HRW) was used to relieve the ROS stress in this study. Our results demonstrate that the treatment of 5% HRW significantly decreased the ROS content, maintained biomass and polar growth morphology of mycelium, and decreased secondary metabolism under HAc‐induced oxidative stress. Furthermore, the roles of HRW were largely dependent on restoring the glutathione system under HAc stress in G. lucidum . To provide further evidence, we used two glutathione peroxidase (GPX)‐defective strains, the gpxi strain, the mercaptosuccinic acid (MS, a GPX inhibitor)‐treated wide‐type (WT) strain, and gpx overexpression strains for further research. The results show that HRW was unable to relieve the HAc‐induced ROS overproduction, decreased biomass, mycelium morphology change and increased secondary metabolism biosynthesis in the absence of GPX function. The gpx overexpression strains exhibited resistance to HAc‐induced oxidative stress. Thus, we propose that HRW regulates morphology, growth and secondary metabolism via glutathione peroxidase under HAc stress in the fungus G. lucidum . Furthermore, our research also provides a method to study the ROS system in other fungi.

Modified approach to evaluation of undrained shear strength from piezocone tests in soft clays - Yaguo Zhang; Jingpei Li; Fayun Liang; Rui Fang; He Li (Marine Georesources & Geotechnology, 2017)

Seroprevalence investigation of bovine ephemeral fever in yaks in Tibetan Plateau of China from 2012 to 2015 - Dongyu Liu; Kun Li; Lihong Zhang; Yanfang Lan; Xiaoqiang Wang; Hui Zhang; Lei Wang; Rui Gui; Zhaoqing Han; Wenteng Jang; Suolang Sizhu; Jiakui Li (Tropical Animal Health and Production, 2017)

Efficient Generation of Functionally Active Spinal Cord Neurons from Spermatogonial Stem Cells - Hao Yang; Cuicui Liu; Bo Chen; Jing An; Rui Zhang; Qian Zhang; Jingjing Zhao; Baorong He; Ding-Jun Hao (Molecular Neurobiology, 2017)

Abnormal O-GlcNAcylation of Pax3 Occurring from Hyperglycemia-Induced Neural Tube Defects Is Ameliorated by Carnosine But Not Folic Acid in Chicken Embryos - Rui-Rong Tan; Yi-Fang Li; Shi-Jie Zhang; Wen-Shan Huang; Bun Tsoi; Dan Hu; Xin Wan; Xuesong Yang; Qi Wang; Hiroshi Kurihara; Rong-Rong He (Molecular Neurobiology, 2017)

MicroRNA-146a Promotes Oligodendrogenesis in Stroke - Xian Shuang Liu; Michael Chopp; Wan Long Pan; Xin Li Wang; Bao Yan Fan; Yi Zhang; Haifa Kassis; Rui Lan Zhang; Xiao Ming Zhang; Zheng Gang Zhang (Molecular Neurobiology, 2017)

Two new compounds from Trollius chinensis Bunge - Ya Jie-Shi; Lin Wei-Sang; Rui Yan; Qiang Zhao; Yang Zhang; Gui Yun-Zhao; Yun Cong-Li; Xue Chen; Chong Yu-Zhang; Hua Qiao; Guo Gang-Zhang (Journal of Natural Medicines, 2017)

Spatial distribution of soil cadmium and its influencing factors in peri-urban farmland: a case study in the Jingyang District, Sichuan, China - Bing Li; Rui Xiao; Changquan Wang; Linhai Cao; Yi Zhang; Shunqiang Zheng; Lan Yang; Yong Guo (Environmental Monitoring and Assessment, 2017)

Paenibacillus oryzisoli sp. nov., isolated from the rhizosphere of rice - Jun Zhang; Xiao-Tong Ma; Jun-Sheng Gao; Cai-Wen Zhang; Juan-Juan Zhao; Rui-Jie Zhang; Li-An Ma; Xiao-Xia Zhang (Antonie van Leeuwenhoek, 2017)

Improved salt tolerance of medicinal plant Codonopsis pilosula by Bacillus amyloliquefaciens GB03 - Qing-Qing Han; Yong-Na Wu; Hui-Juan Gao; Rui Xu; Paul W. Paré; Huazhong Shi; Qi Zhao; Hui-Ru Li; Sardar Ali Khan; Yin-Quan Wang; Suo-Min Wang; Jin-Lin Zhang (Acta Physiologiae Plantarum, 2017)

The potential of foxtail millet as a trap crop for sunflower broomrape - Xiaoxin Ye; Jie Chen; Christopher S. P. McErlean; Meng Zhang; Rui Yu; Yongqing Ma (Acta Physiologiae Plantarum, 2017)